Human adipose‐derived multipotent stromal cells enriched with IL‐10 modRNA improve diabetic wound healing: Trigger the macrophage phenotype shift - Yuxin Zhang; Wei Wang; Liang Chen; Heng Wang; Dong Dong; Jingjing Zhu; Yu Guo; Yiqun Zhou; Tianyi Liu; Wei Fu (Bioengineering & Translational Medicine)
Abstract Diabetic wounds present a significant challenge in regenerative medicine due to impaired healing, characterized by prolonged inflammation and deficient tissue repair, primarily caused by a skewed pro‐inflammatory macrophage phenotype. This study investigates the therapeutic potential of interleukin‐10 (IL‐10) chemically modified mRNA (modRNA)‐enriched human adipose‐derived multipotent stromal cells (hADSCs) in a well‐established murine model of diabetic wounds. The modRNAs used in this study were chemically modified using N1‐methylpseudouridine‐5′‐triphosphate (m1Ψ) by substituting uridine‐5‐triphosphate. In vitro experiments demonstrated that IL‐10 modRNA‐transfected hADSCs effectively modulated macrophage polarization towards an anti‐inflammatory phenotype. In vivo experiments with a well‐established murine model demonstrated that transplantation of hADSCsmodIL‐10 on postoperative day 5 (POD5) significantly improved wound healing outcomes, including accelerated wound closure, enhanced re‐epithelialization, promoted M2 polarization, improved collagen deposition, and increased neovascularization. This study concludes that IL‐10 modRNA‐enriched hADSCs offer a promising therapeutic approach for diabetic wound healing, with the timing of IL‐10 administration playing a crucial role in its effectiveness. These cells modulate macrophage polarization and promote tissue repair, demonstrating their potential for improving the management of diabetic wounds.